2018
DOI: 10.3892/ol.2018.8899
|View full text |Cite
|
Sign up to set email alerts
|

Pachymic acid inhibits growth and induces cell cycle arrest and apoptosis in gastric cancer SGC‑7901 cells

Abstract: The aim of the present study was to elucidate the anticancer effect of pachymic acid (PA) in gastric cancer SGC-7901 cells and the potential molecular mechanisms involved. Cell Count kit-8 assay was performed to examine the effect of PA on the cell proliferation of SGC-7901 cells. Cell cycle, cell apoptosis, mitochondria membrane potential (Dψm) and reactive oxygen species (ROS) analysis were assessed by flow cytometry, respectively. DNA fragmentation assay was performed by Hoechst 33258 staining. Western blot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…To investigate the effect of miR-224 on Bcl-2/Bax and PI3K signalings, we analyzed the expression of PI3K and p-PI3K in miR-224-transfected A549 cells. As shown in Figure 6A–F, miR-224 overexpression up-regulated expression of anti-apoptosis related Bcl-2 and down-regulated expression of pro-apoptosis-related Bax,17,18 whose effects were reversed by the miR-224 inhibitor. Moreover, similar effects were noted for protein expression levels of PI3K and AKT; however, a significant increase in protein expression of p-PI3K-p85 and p-AKT was induced by miR-224 mimic, and reduction in p-PI3K-p85 and p-AKT expression was observed in A549 cells transfecting with miR-224 inhibitor (Figure 6G–J, p <0.01).…”
Section: Resultsmentioning
confidence: 92%
“…To investigate the effect of miR-224 on Bcl-2/Bax and PI3K signalings, we analyzed the expression of PI3K and p-PI3K in miR-224-transfected A549 cells. As shown in Figure 6A–F, miR-224 overexpression up-regulated expression of anti-apoptosis related Bcl-2 and down-regulated expression of pro-apoptosis-related Bax,17,18 whose effects were reversed by the miR-224 inhibitor. Moreover, similar effects were noted for protein expression levels of PI3K and AKT; however, a significant increase in protein expression of p-PI3K-p85 and p-AKT was induced by miR-224 mimic, and reduction in p-PI3K-p85 and p-AKT expression was observed in A549 cells transfecting with miR-224 inhibitor (Figure 6G–J, p <0.01).…”
Section: Resultsmentioning
confidence: 92%
“…Poria ethanol extract treatment alleviated the damage to the liver and normalized the serum levels of ALT and AST in mice compared with the mice with cisplatin treatment [73]. e study showed that PA could induce apoptosis of SGC-7901 cells by inactivating the JAK2/STAT3 signaling pathway, which proved that PA was a potential bioactive substance for the treatment of gastric cancer [74]. PA could induce caspase 3-mediated apoptosis of HOS and primary osteosarcoma cells by increasing PTEN expression and inhibiting Akt activation [75].…”
Section: E Antitumor Effect Of Poriamentioning
confidence: 87%
“…Moreover, Compound 1 regulated the expression of apoptosis-related proteins (caspase-3, PARP, Bcl-2, and Bax), suppressed the mitochondrial capacity of gastric cancer cells dose-dependently and finally induced cell apoptosis in vitro . Furthermore, compound 1 inhibited the tumor growth of xenograft models of gastric cancer and promoted the survival of animals obviously ( Lu et al, 2017 ; Sun and Xia, 2018 ). In addition, compound 1 might inhibit tumorigenesis of gastric cancer cells through up-regulating the expression of Bax by suppressing hypoxia/HIF1α ( Lu et al, 2018 ).…”
Section: Pharmacological Activities and Toxicological Informationmentioning
confidence: 99%
“…According to the existing research literature, it can be clearly seen that the main active constituents of Poria cocos are concentrated on triterpenes and polysaccharides ( Jia et al, 2016 ). Some of these constituents possessed a series of biological activities including anti-tumor ( Sun and Xia, 2018 ), hepatoprotective ( Wu et al, 2019 ), anti-inflammatory ( Lee et al, 2017 ), anti-oxidant ( Wang et al, 2016 ), anti-bacterial ( Wang et al, 2019a ), immunomodulation( Pu et al, 2019 ), etc. Therefore, these complex chemical compounds and pharmacological effects of Poria cocos attracted researcher’s considerable attention, meanwhile, they also brought huge challenges for research.…”
Section: Introductionmentioning
confidence: 99%